2020
DOI: 10.1016/j.jcf.2019.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab for asthma and allergic bronchopulmonary aspergillosis in adults with cystic fibrosis

Abstract: Background: In cystic fibrosis (CF), omalizumab has been used for difficult-to-treat asthma and allergic bronchopulmonary aspergillosis (ABPA) but safety and efficacy data are limited for this population. Methods: We assessed patients receiving omalizumab for asthma or ABPA in the Toronto adult CF center between 2005 and 2017. We evaluated treatment safety and efficacy by analyzing changes in FEV 1 % predicted (FEV 1 pp) max value, slope and variability captured by the area under the curve (AUC), the cumulativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…At baseline the median for FEV1 (% predicted) was 58% (range 24.36–76.2), 9 11 , 14 22 , 34 , 36 38 and after 3 months to 3 years of follow-up FEV1 had a median of 62% of the predicted value (range 35.6–90). 9 , 10 , 14 , 16 – 19 , 21 , 22 , 34 , 36 , 38 Three studies reported the value in liters at baseline and after treatment with a median of 2.28 L (range 1.36–5.3) pre-treatment and a median of 2.4 L (range 1.5–5.5) post-treatment. 11 , 20 , 37 …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…At baseline the median for FEV1 (% predicted) was 58% (range 24.36–76.2), 9 11 , 14 22 , 34 , 36 38 and after 3 months to 3 years of follow-up FEV1 had a median of 62% of the predicted value (range 35.6–90). 9 , 10 , 14 , 16 – 19 , 21 , 22 , 34 , 36 , 38 Three studies reported the value in liters at baseline and after treatment with a median of 2.28 L (range 1.36–5.3) pre-treatment and a median of 2.4 L (range 1.5–5.5) post-treatment. 11 , 20 , 37 …”
Section: Resultsmentioning
confidence: 98%
“…We found a total of 17 studies which included 104 patients. 9 11 , 14 22 , 34 38 Seven were case series, defined as ⩾three patients, nine were case reports and one was a randomized double-blind cross-over study; 89 patients (85.5%) were on long-term systemic steroids at the time of initiation of Omalizumab, 14 patients were not receiving steroids (9.2%) and in one case it was not reported. Follow-up ranged from 3 months to 3 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since IgE-mediated hypersensitivity is involved in ABPA pathogenesis, omalizumab (i.e., a humanized monoclonal antibody against IgE) use has been proposed for ABPA in CF patients [ 68 , 69 ]. Perisson et al retrospectively analysed 18 patients and observed a stabilization in lung function decline after the initiation of biological therapy with omalizumab along with a notable reduction in the corticosteroid daily dose needed and an improvement in the nutritional status [ 70 ].…”
Section: Treatment Of Abpa In Patients With Cfmentioning
confidence: 99%